TILLAGE PRACTICES AFFECT THE WATER CONSERVATION BENEFITS OF RAINWATER HARVESTING IN SEMI-ARID CONDITIONS - RIZVI, SA; NASEEM, W; MUHAMMAD, G; ANJUM, S; HUSSAIN, T; RAFIQUE, R; LATIEF, N; UMAIR, A (Biological and Clinical Sciences Research Journal, 2023)
Livelihood in the Pothwar region of Pakistan is largely dependent on rainwater. Therefore, storing and conserving rainwater for its subsequent use when required is crucial. Amongst various means of in-field moisture conservation, tillage practices play a dynamic role, especially in loose soils of Pothwar area. Under this study, the efficiency of commonly used tillage implements i.e., mould board (MB) plough, disc plough and cultivator, was evaluated for moisture conservation and improvement in wheat (Triticum aestivum L) yield. The three years’ study showed that maximum soil moisture and grain yield were obtained in the field tilled with MB plough followed by disc plough. It has been observed that soil water was improved by 11.3, 10.6, 9.9 and 11.5 % in the treatment of MB plough, while this increase was recorded as 5.7, 9.0, 5.2 and 6.8 % in disc plough as compared to cultivator at sowing, 02 months & 04 months after sowing and harvesting stage, respectively. In the treatment of MB plough, improvements were observed as a wheat grain yield 16%, wheat straw yield 19%, productive tillers 6% and plant height by 2%. Furthermore, MB plough enhanced its productivity and profitability with the highest benefit-cost ratio of 1.83. The role of disc plough in soil water conservation and crop productivity enhancement was observed less than MB plough. The current study observed that use of MB plough is beneficial in soil water conservation and improvement of crop yield.